The Optimization of Financial Management Rooted in Local Wisdom to Improve the Quality of Islamic Educational Institutions in Madrasahs - Ridwan Idris; Caroline Teresa Linse; Lisa Nursita (Idarah (Jurnal Pendidikan dan Kependidikan), 2025)
Financial management plays a strategic role in ensuring the effectiveness and quality of Islamic educational institutions, especially private madrasahs that depend heavily on School Operational Assistance (BOS) funds. This study explores the financial management practices at MTs Ash-Shalihin Gowa, focusing on how strategies grounded in local wisdom and Islamic values help address funding limitations without compromising educational quality or sustainability. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis. Key informants included the head of the foundation, the principal, and the treasurer, who provided insights into the planning, budgeting, control, and evaluation processes. Thematic analysis was used, and findings were validated through triangulation. Results show that effective financial management in the madrasah is built on collaborative governance that incorporates local wisdom, such as gotong royong (mutual cooperation), musyawarah (deliberation), and religious values like amanah (trust) and barakah (spiritual benefit). Budgeting was based on needs and priorities, supported by inclusive decision-making involving all stakeholders. The use of the digital E-RKAM system improved transparency and accountability yet was applied in a way that respected the madrasah’s ethical and religious culture. Regular internal and external evaluations supported a reflective and adaptive financial cycle. These evaluations extended beyond regulatory compliance and included community feedback, reinforcing the institution’s legitimacy and responsiveness. Financial efficiency was thus viewed not merely as cost-saving but as a form of ethical stewardship (khalifah) over communal resources. This study contributes to the theory of Islamic educational financial management by showing how local wisdom can enhance digital governance. It offers a practical model for other madrasahs to replicate, emphasizing the importance of aligning religious values, digital tools, and cultural practices in improving educational quality sustainably.